In Vitro Oocyte Maturation: Current Status - Nogueira, Daniela; Sadeu, Jean Clair; Montagut, Jacques (Seminars in Reproductive Medicine, 2012)
Due to its numerous clinical applications, in vitro maturation (IVM) has emerged as a significant topic in the field of assisted reproduction. IVM of germinal vesicle breakdown/metaphase I and germinal vesicle stage oocytes collected from in vitro fertilization (IVF) superovulation cycles are commonly applied with unsatisfactory results. The biological aspect of this so-called rescue in vitro oocyte maturation greatly differs from the actual IVM practice. In the latter, immature oocytes are obtained from small antral follicles of unprimed or minimally stimulated cycles aiming to avoid ovarian hyperstimulation syndrome in high-risk patients or simply as an alternative to conventional IVF in normo-ovulatory patients. Over the past decade, cases reports regarding IVM have been sporadically reported, with ~25 peer-reviewed articles currently available. These studies present variable outcomes and deal with clinical approaches about selecting the most appropriate patient population that could benefit from IVM technology. Although some of the studies are encouraging, the vast majority includes small sample sizes, thus making the data rather inconclusive. As such there is a certain reserve in the IVF community to embark on treatment cycles for IVM in routine use. Laboratory parameters play an important role in the success of IVM, and research for optimal culture conditions is warranted. Existing data from newborns assure us that IVM may be a safe procedure provided in assisted reproductive technology. When optimized, it will serve, not only for infertile patients, but also as a more patient-friendly alternative than standard controlled ovarian stimulation to obtain oocytes for donation or preservation of fecundity.
Keywords: In vitro maturation; immature oocytes; IVM; oocyte maturation; assisted reproductive technologies